Основні завдання ефективної соціальної політики в умовах глобалізації та демократичних трансформацій - Конончук, Олександр Григорович; Kononchuk, Oleksandr G. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розглянуто проблеми ефективності соціальної політики як фактора демократичних трансформацій суспільства, а також способи їх розв’язання в сучасних умовах. Пояснено категорії «соціальна політика» у вузькому та широкому його значеннях, а також продемонстровано необхідність вивчення сфери соціальної політики як у теоретичному, так і в практичному вимірах. У дослідженні розкрито основні недоліки ефективності соціальної політики, особливу увагу звернуто на проблеми, які простежуємо в соціальній політиці України. Відзначено, що концептуально демократичні трансформації мають безпосередній зв’язок із політикою сталого розвитку, важливим складником якої є ефективна соціальна політика. В умовах глобалізації соціальна політика набуває значення глобальної політики в рамках діяльності ООН (свідчення цього – програми ООН «Цілі розвитку тисячоліття» (2000–2015 рр.) та «Цілі сталого розвитку» (2016–2030 рр.)) й інших міжнародних організацій, мета яких – подолання глобальних розривів в економічному, політичному, культурному та соціальному розвитку країн світу.The article deals with the problems of the effectiveness of social policy as a factor of democratic transformations of society and their solutions in modern conditions. The author gives an explanation of the category of «social policy» in the narrow and broad sense, and demonstrates the need to explore areas of social policy in theoretical and practical dimensions. The study reveals major shortcomings of the effectiveness of social policy; special attention is paid to the problems that are present in the social policy of Ukraine. It is noted that conceptually democratic transformations have a direct link to the policy of sustainable development, an important component of which is effective social policy. Under the conditions of globalization social policy becomes important global policy within the framework of the United Nations (evidenced by the UN «Millennium Development Goals» (2000–2015) and «The goals of sustainable development» (2016–2030)) and other international organizations, aimed at overcoming of the global gaps in economic, political, cultural and social development of the countries of the world. It is made the conclusion that one of the main objectives of social policy in the world and in Ukraine is to overcome poverty and its manifestations and consequences for different groups. Another important tasks of the effective social policy in Ukraine in the context of globalization and democratic transformations are: reforming of the social welfare system; overcoming of the demographic crisis; minimizing of manifestations of negative social phenomena like teenage delinquency, drug abuse, HIV / AIDS, the problem of migrants and internally displaced persons, disadvantaged families, child neglect, etc; achieving peace, harmony in society and overcoming of destructive consequences of the political crisis of recent years; development and implementation of the National Program of sustainable development in Ukraine.
The Main Objectives of Effective Social Policy under the Conditions of Globalization and Democratic Transformations
Keywords: ефективність соціальної політики; сталий розвиток; бідність; соціальне забезпечення; effectiveness of social policy; sustainable development; poverty; welfare